REGIMES OF KNOWLEDGE/POWER IN DISCO REGIMES OF KNOWLEDGE/POWER IN DISCOURSE ABOUT EVALUATION OF EXTENSIONURSE ABOUT EVALUATION OF EXTENSION - Celso Kraemer; Jeice Campregher (Editora da Universidade de Santa Cruz do Sul, 2017)
This article discusses the regimes of power/knowledge in actuation in the discourses about evaluation of the University Extension activity. The methodological basis is archeology and genealogy of Foucault. The material analised was extracted in a form where teachers proposed extension projects to be developed in a University of Santa Catarina. These are excerpts from discourse that enable rich analysis of regimes of knowledge/power in actuation in University Extension activity. The main questions is: What are the internal and external mechanisms that regulate the teachers' responses to a institucional form about the evaluation of extension students? The objetive is to analyze the discourse on evaluation of extension students, regimes of knowledge/power that make it possible. What the analysis showed: the place institutional regulates discourse; there is asymmetry between institutional subjects, disciplinary power devices operate on the evaluation, it implies forms of conduction of conduct, the participation concept reflects a change of the disciplinary regime for flexible power called control. Keywords: Disciplinary regime. Control regime. Discourse Analysis. Evaluation of the activity of University Extension.